Who can afford to dissent at work? The mediating effect of organizational socialization on the relationship between social capital and organizational dissent - Ak, Murat; Turkmenoglu, Mehmet Ali; Acar, Duygu; Ramiz Hacarlioglu, Abdullah; Ozbilgin, Mustafa (Frontiers in Psychology, 2024)
This study aims to empirically examine whether organizational socialization has a mediating effect on the relationship between social capital and organizational dissent. Quantitative data has been collected from employees within the textile in Turkey. According to the results of the SEM, social capital positively affects organizational dissent. Similarly, social capital positively affects organizational socialization. The mediation level of organizational socialization is at the level of partial mediation on the relationship between social capital and organizational dissent. Based on the results, organizational socialization positively affects organizational dissent. We contribute to the literature by extending social capital research by illustrating that employees' social relationships lead to organizational socialization and organizational dissent behavior at work. The results suggest that the ability of employees to show dissent behavior is conditioned by their social capital and mediated by organizational socialization.